"It was the President's decision to make, and he made it" : Legitimization in Articles about Trump's Pullout from Syria - Vehniäinen, Santtu (My University, 2024)
In this study, several newspaper articles about President Donald Trump’s choice to withdraw from Syria in 2018 are analyzed to research legitimization in journalism. This study used van Leeuwen’s framework to categorize and quantify the methods of legitimization used within the articles, and the results were then put together and analyzed. The study regarded legitimization as a form of persuasion and a manifestation of ideological and power relationships. The main outcomes of this analysis were a clear prevalence in the use of instrumental rationalizations and expert authority to delegitimize the withdrawal, and a correlation between explanations and predictions. All of the analyzed articles were also clearly delegitimizing Trump’s choice, although to a different degree. These results show a hidden type of political bias within news reporting that arises from the common use of quotations and regarding various actors as essentialized in their characteristics. Further research to this topic is needed particularly on the connections between expert authority and quotations in newspaper discourse, and well as on the correlation between characterizations of actors and predictions based on those explanations.
Keywords: Critical Discourse Analysis, Speech Act Theory, Legitimization, Rationalization, Authorization, Morality, Mythopoesis, Discourse, Politics